Impact Analysis of Adiwiyata Program Implementation in Developing Students' Pro-Environmental Attitudes in Elementary Schools - Wanti, Astika Berliana; Murtadho, Nurul; Widiyanti, Widiyanti (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
This study examines the role of the Adiwiyata program in shaping pro-environmental attitudes in elementary school students. The urgent need for effective environmental education to raise awareness from an early age motivated this research. Using a descriptive qualitative approach and a multisite study design, data were collected through observation, interviews and documentation. The research sample consisted of three elementary schools that have implemented the Adiwiyata program: SDIT Ahmad Yani, SDN Percobaan 2, and SDN Lowokwaru 2. Data analysis was conducted using cross-site analysis and data validity was guaranteed through triangulation. The results showed that the implementation of the Adiwiyata program through initiatives such as the formation of wiyata cadres, waste management, and environmentally friendly activities succeeded in increasing students' awareness and participation in protecting the environment. Factors such as physical readiness, administration, aligned vision and mission, educators' involvement, as well as school community support are critical to the success of this program. This study concludes that a gradual and experiential learning approach can improve students' understanding and involvement in environmental conservation. The study suggests improving the school's green infrastructure, continuous training for educators, strengthening student engagement through interactive activities, school policy support, regular evaluation of the program, and collaboration with the community. Implementation of these recommendations is expected to strengthen the effectiveness of the Adiwiyata program and expand its impact on education.